Strategies and Factors to Promote Research in Primary Care in Portugal: A Cross-Sectional Study - Morgado, Maria Beatriz (2025)
Introduction: Research is crucial for building an efficient health system care. This reality is particularly evident in primary care, the cornerstone of healthcare services. However, research in primary care is not consistently implemented across Europe. With this study we aimed to: 1) identify the factors and strategies that healthcare professionals consider relevant for promoting research in primary care in Portugal; 2) analyze whether the prioritized strategies vary according to the geographical area, professional group, workplace, interest, and experience in research of the participants.Methods: We conducted an analytical cross-sectional study using an online survey applied in the first semester of 2023. We designed the survey based on strategies identified in a previous qualitative study. We included health professionals working in Primary Care in Portugal (continental and autonomous regions). We intended to obtain at least 200 answers for each professional category and geographical area. The survey was initially sent to a convenience sample to assess the acceptability and interpretation of the questions. We then disseminated the survey through all national Health Center Clusters and through professional associations. We conducted an analysis using a 5% significance level.Results: The sample consisted of 1027 participants: 507 doctors, 377 nurses, 106 diagnostic and therapeutic technicians, and 30 secretaries. The majority worked in the Lisbon and Tagus Valley region (51.9%), followed by the North (22.1%) and Centre (17.1%). Around half of the participants worked in a Family Health Unit, 16.5% worked in a Personalized Healthcare Unit, 11% in a Community Care Unit, and 8.7% in a Public Health Unit. The factors promoting research mentioned by a greater proportion of participants were research training (76%), access to mentors (71%) and grants (56%). As for strategies to promote research, most participants supported the existence of dedicated time for research (82%), public grants (65%), institutional support (51%), access to support services (58%) and research data (57%).Conclusion: There seems to be a consensus on which factors are currently promoting research and what future strategies might be useful for promoting research in primary care in Portugal. Nevertheless, there are some differences between certain sub-groups. This information might be useful to tailor initiatives directed at specific sub-groups. Our intention is to help form policies and strategies to promote research in primary care in Portugal, contributing to the national development on the subject.